Review paper Vitamin D impact on immune functions: implications for preventive strategy of allergic disease? - Szczawińska-Popłonyk, Aleksandra; Bręborowicz, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Asthma and allergic diseases are substantial global health problems with a higher prevalence in the westernized countries. It has been proposed that vitamin D deficiency resulting from reduced exposure to sunlight and changes in lifestyle as well as dietary habits may contribute to a high prevalence of asthma and allergic diseases. This review examines the scientific evidence for pluripotent immunoregulatory actions of vitamin D in conjunction with nuclear actions as well as genetic and epigenetic determinants of the vitamin D effects. Findings of epidemiological and clinical studies on the potential association between vitamin D and allergic disease and asthma are reviewed.